Hubungan Kelengkapan Imunisasi Dasar dengan Kesehatan Anak Usia 1-5 Tahun di Desa Sukomulyo - Wiladatul Hosnaniah; Mutmainnah Zakkiyyah; Tutik Ekasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Immunization is the basis for effective disease prevention in children under the age of five to protect a person from dangerous diseases before coming into contact with disease-causing agents, Efforts to actively increase a person's immunity to a disease so that if one day they will get sick or only experience mild illness. The purpose of this study was to determine the Relationship between Completeness of Basic Immunization and Children Aged 1-5 Years in Sukomulyo Village. This study uses the Correlational Analytical method using the Cross-sectional approach where data collection is only carried out at one time or once. The sample is some children aged 1-5 years, totaling 137 using the Random Sampling Technique. The instrument used is the KIA book record. The results of this study indicate that the status of completeness of basic immunization in Sukomulyo village is mostly complete (33.8%), and the health status of children in Sukomulyo village is mostly sick (50.4%). based on the results of the chi-square statistical test, a p-value of 0.000 was obtained, which means that there is a Relationship between Completeness of Basic Immunization and the Health of Children Aged 1-5 Years in Sukomulyo Village. Advice for people who have children to carry out complete basic immunization so that they know the importance of children's health and the knowledge of mothers in immunizing their children.